Development Of Sakukha Culture In The Lampung Saibatin Tribe Community (1993-2017): Material Contribution To The Course Of Cultural History Of History Education Of Sriwijaya University - Eka Stiawati; Syafruddin Yusuf; Alian Alian (Criksetra: Jurnal Pendidikan Sejarah, 2018)
This thesis entitled Development Of Sakukha Culture In Lampung Saibatin Tribe Society (1993-2017): (Material Countribution To Cultural History Courses Historical Education Sriwijaya University). Sakukha is a mask party that is held every five days after Idul Fitri day, alternating from village to village, as an expression of joy after a month full of fasting Ramadan. The problems discussed by the author is how the culture of sakukha. How the development of culture of sakukha in Lampung tribe society saibatin 1993-2017. How are the values in the culture of sakukha. The purpose of this research is to know the culture of sakukha. The development of culture of sakukha in Lampung tribe society saibatin 1993-2017, values in the culture of sakukha. The method of writing used is the historical method, using the steps of Heuristics, Source Criticism, Interpretation, and Historiography.